1984
DOI: 10.1002/jnr.490120220
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan fluorescence properties of cholera toxin upon interacting with ganglioside GD1b

Abstract: A blue shift of the tryptophan fluorescence emission spectra of cholera toxin or the B protomer is induced by disialoganglioside GD1b with a capacity similar to that of monosialoganglioside GM1. Both gangliosides were also capable of decreasing or reversing the fluorescence quenching by iodide ion of the toxin. The quenching constants (Ksv) for the toxin fluorescence in absence of gangliosides was 2.8 M-1; in presence of GM1 or GD1b, Ksv was 0.8 M-1 and 0.7 M-1, respectively. Gangliosides GD1a and GT1b were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The appearance of signal corresponding to GD1a/b is consistent with the results of previously reported binding experiments that identified GD1b as a low affinity ligand for CTB 5 . 34,40,41 Direct ESI-MS binding measurements performed on solutions of CTB 5 with GD1a or GD1b revealed that GD1b binds with a measurable affinity, while GD1a does not bind (data not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The appearance of signal corresponding to GD1a/b is consistent with the results of previously reported binding experiments that identified GD1b as a low affinity ligand for CTB 5 . 34,40,41 Direct ESI-MS binding measurements performed on solutions of CTB 5 with GD1a or GD1b revealed that GD1b binds with a measurable affinity, while GD1a does not bind (data not shown).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…It is generally accepted that the monosialoganglioside GM1 is the toxin receptor in the intestine of several animal species including humans (6,16,19). Recently, it has been shown that other gangliosides such as GDlb (8,15,23), fucose-GM1 (18), and galactose-N-acetylgalactosamine-GM1l (26) show considerable capacity to bind CT when assayed in vitro. Even if some of these latter gangliosides are also present in intestinal epithelial cells, a receptor capability leading to an increase in cyclic AMP concentration has not yet been demonstrated for any of them.…”
mentioning
confidence: 99%